Side Effect Patterns in a Crossover Trial of Statin, Placebo, and No Treatment - Howard, James P; Wood, Frances A; Finegold, Judith A; Nowbar, Alexandra N; Thompson, David M; Arnold, Ahran D; Rajkumar, Christopher A; Connolly, Susan; Cegla, Jaimini; Stride, Chris; Sever, Peter; Norton, Christine; et al. (Journal of the American College of Cardiology, 2021)
Most people who begin statins abandon them, most commonly because of side effects. The purpose of this study was to assess daily symptom scores on statin, placebo, and no treatment in participants who had abandoned statins. Participants received 12 1-month medication bottles, 4 containing atorvastatin 20 mg, 4 placebo, and 4 empty. We measured daily symptom intensity for each using an app (scale 1-100). We also measured the "nocebo" ratio: the ratio of symptoms induced by taking statin that was also induced by taking placebo. A total of 60 participants were randomized and 49 completed the 12-month protocol. Mean symptom score was 8.0 (95% CI: 4.7-11.3) in no-tablet months. It was higher in statin months (16.3; 95% CI: 13.0-19.6; P < 0.001), but also in placebo months (15.4; 95% CI: 12.1-18.7; P < 0.001), with no difference between the 2 (P = 0.388). The corresponding nocebo ratio was 0.90. In the individual-patient daily data, neither symptom intensity on starting (OR: 1.02; 95% CI: 0.98-1.06; P = 0.28) nor extent of symptom relief on stopping (OR: 1.01; 95% CI: 0.98-1.05; P = 0.48) distinguished between statin and placebo. Stopping was no more frequent for statin than placebo (P = 0.173), and subsequent symptom relief was similar between statin and placebo. At 6 months after the trial, 30 of 60 (50%) participants were back taking statins. The majority of symptoms caused by statin tablets were nocebo. Clinicians should not interpret symptom intensity or timing of symptom onset or offset (on starting or stopping statin tablets) as indicating pharmacological causation, because the pattern is identical for placebo. (Self-Assessment Method for Statin Side-effects Or Nocebo [SAMSON]; NCT02668016).